Mobility under the COVID-19 Pandemic : Asymmetric Effects across Gender and Age - Caselli, Francesca; Grigoli, Francesco; Sandri, Damiano; Spilimbergo, Antonio (Washington, D.C. : International Monetary Fund, 2020)
Lockdowns and voluntary social distancing led to significant reduction in people's mobility. Yet, there is scant evidence on the heterogeneous effects across segments of the population. Using unique mobility indicators based on anonymized and aggregate data provided by Vodafone for Italy, Portugal, and Spain, we find that lockdowns had a larger impact on the mobility of women and younger cohorts. Younger people also experienced a sharper drop in mobility in response to rising COVID-19 infections. Our findings, which are consistent across estimation methods and robust to a variety of tests, warn about a possible widening of gender and inter-generational inequality and provide important inputs for the formulation of targeted policies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet